What Does Teacher’s Perception of Feedback in EFL Classroom? Insights From Non-Formal Education Institution - Hidayat, Muhammad; Mursyid, Andi Miftahul Maulidil (Lembaga Intelektual Muda (LIM) Maluku, 2023)
Many studies in teachers’ perception of feedback have been done in mostly government educational institution. Otherwise, studies investigating the teachers’ perception in non-formal education setting is still insufficient. This study aims to analyze EFL teachers’ perception of feedback at non-formal education institutions. The data used in the research were assembled for about 2 months, starting from January to March 2023, and they were collected through observation and sharing questionnaires via google form. The participants were 8 English teachers. In addition, this qualitative research used thematic analysis to analyze the data. Based on the data analysis, this study revealed that providing feedback to students in EFL classroom is important and it should be mandatory. Also, students’ will not get any insight of their academic performances if teachers do not provide any feedback for them. At last, feedback process is best to give at the end of every session. The other issues are also discussed here